Women’s perception of accuracy of ultrasound dating in late pregnancy: a challenge to prevention of prolonged pregnancy in a resource-poor Nigerian setting - Ugwu EO; Odoh GU; Dim CC; Obi SN; Ezugwu EC; Okafor II (Dove Medical Press, 2014)
Emmanuel O Ugwu,1 Godwin U Odoh,1 Cyril C Dim,1 Samuel N Obi,1 Euzebus C Ezugwu,1 Innocent I Okafor21Department of Obstetrics and Gynaecology, University of Nigeria Teaching Hospital, Ituku/Ozalla, Enugu, Nigeria; 2Department of Obstetrics and Gynaecology, Enugu State University Teaching Hospital, Parklane, Enugu, NigeriaBackground: Expected date of delivery (EDD) is estimated from the last menstrual period (LMP) or ultrasound scan. Conflicts between these estimates especially on the part of the physician and his/her patient could pose a challenge to prevention of prolonged pregnancy. The objective of this study was to determine the perception and acceptability of menstrual dating (EDD derived from LMP) with regard to timing of labor induction for postdatism by pregnant women who have a late pregnancy (≥23 weeks’ gestation) ultrasound scan.Methods: This cross-sectional study included 443 consecutive pregnant women receiving antenatal care at two tertiary health institutions in Enugu, Nigeria, from January 1, 2013 to March 31, 2013.Results: The mean age of the women was 27.9±2.41 (range 17–45) years. Most ultrasound scans (90.8%, 357/389) were carried out in late pregnancy, and 41.9% (167/389) were self-referred. The majority of the respondents (51.7%, 229/443) did not accept induction of labor for postdatism at a certain menstrual dating-derived gestational age of 40 weeks plus 10 days if the late pregnancy ultrasound scan dating was less. Predictors of this poor attitude to timing of induction of labor for postdatism included low educational level, low social class, and poor knowledge of the limitations of ultrasound scan dating in late pregnancy (P<0.05).Conclusion: The worrisome confidence in ultrasound scan dating is a challenge to the prevention of prolonged pregnancy and its complications in our environment. Antenatal health education should discourage self-referral for ultrasound scan dating and emphasize its limitations in late pregnancy as well as the perinatal effects of prolonged pregnancy.Keywords: ultrasound dating, prolonged pregnancy, Nigeria